The Use of Mathematics Taxonomy in Developing Statistical Learning Outcomes for Grade 12 Learners - Kalobo, Lukanda; du Toit, Gawie Francois (International Journal of Educational Sciences, 2015)
In this paper the use of Mathematics taxonomy in developing statistical learning outcomes (SLO) for Grade 12 learners is investigated. A literature on Mathematics taxonomy and the SLO was reviewed. Further, a case was made for using the Mathematics taxonomy and the SLO in writing assessment tasks in teaching statistics. It is argued that Mathematics taxonomy uses four cognitive levels, knowledge, routine procedures, complex procedures and solving problem to guide all the assessment tasks. Furthermore, it is argued that the use of the three SLO, statistical literacy, reasoning and thinking to distinguish between learning outcomes is helpful in teaching statistics. A qualitative content analysis obtained from the 2010 and 2011 Grade 12 mathematics examination papers was done to examine the use of Mathematics taxonomy in developing the SLO. Results showed that the Mathematics taxonomy should be used in developing statistical literacy, reasoning and thinking. Mathematics teachers should be trained to usethe Mathematics taxonomy and the SLO in statistics assessment tasks
Published Article
Keywords: Mathematics Cognitive Levels; Statistical Cognitive Outcomes